Analys av sambandet mellan en skogsfastighets förmåga att generera avkastning och dess läge i landet - Andersson, Filip (SLU/School for Forest Management, 2018)
The market price of a forest property rarely corresponds with the forest property’s return value. This discrepancy is usually being explained by what is called non-monetary values. By that means values that doesn’t generate returns in money, for example pride of ownership. A forest property’s ability to generate returns is related to several factors that are highly correlated with latitude, such as site fertility, average price of forest estates etc.